CIEMER in action: from development to application of a co-creative, interdisciplinary exergame design process in XR - Retz, Celina; Klotzbier, Thomas Jürgen; Ghellal, Sabiha; Schott, Nadja (Frontiers in Virtual Reality, 2024)
Introduction: Motor-cognitive learning is crucial for achieving and maintaining well-being. Exergames can effectively facilitate this type of learning due to their inherent qualities of exertion and game-related disciplines. These qualities can create effectiveness, enjoyment, and meaning in the lives of individuals. \hl{To address these aspects equally, the design process for exergame interventions needs to be interdisciplinary from the beginning.} Objective: This paper aims to (1) enhance an exergame design process model for interdisciplinary co-creation (CIEM) by an Extended Reflection part (CIEMER). Furthermore, it aims to (2) show a formal process for making the abstract model applicable. In doing so, (3) this paper will also derive methods for conducting the process in an academic seminar. Methods: The study employed the CIEMER framework to conduct a two-month academic seminar with 20 students. The seminar consisted of a three-day intensive workshop, a six-week work phase, and a one-week testing phase, creating four Extended Reality prototypes. We used a mixed methods approach to evaluate the model, including feedback interviews with external experts, internal surveys, and written reflections from student designers. Results: Four motor-cognitive learning prototypes in Extended Reality were created using the CIEMER. External expert evaluations highlighted the prototypes' alignment with effective, enjoyable, and meaningful objectives and potential efficacy while noting shortcomings in discipline-specific theoretical application. Internal feedback from students, collected via surveys and reflections, consistently showed positive outcomes in interdisciplinary collaboration and learning, underscoring the importance of an integrated approach in achieving project goals. Conclusion: The formal process within CIEMER effectively yielded four promising prototypes, demonstrating its sufficiency. Students positively acknowledged the benefits of interdisciplinary collaboration, finding it supportive and competence-enhancing. Additionally, the Extended Reflections enabled rapid and targeted iterations, streamlining the reflection of the current state and Creation process.